THU0563 COMPARISON BETWEEN PATIENTS WITH IDIOPATHIC PULMONARY FIBROSISAND INTERSTITIAL PNEUMONIA WITH AUTOIMMUNE FEATURES: A PROSPECTIVE COHORT. (June 2019) - Sambataro, Gianluca; Sambataro, Domenico; Torrisi, Sebastiano Emanuele; Ada, Vancheri; Pavone, Mauro; Pignataro, Francesca; Papa, Nicoletta Del; Palmucci, Stefano; Vanchieri, Carlo; Malatino, Lorenzo; Colaci, Michele
Abstract : Background: The term "Interstitial Pneumonia with Autoimmune Features (IPAF)" is used to describe patients with Interstitial Lung Disease in combination to clinical, serological and/or pulmonary features that are suggestive, but insufficient to satisfy classification criteria of a specific Connective Tissue Disease (CTD). Some retrospective studies available in literature described patient cohorts with IPAF heterogenous in terms of clinical, serological, and radiographic manifestations Objectives: To prospectively recruit a cohort of consecutive ILD patients classified as IPAF or as affected by Idiopathic Pulmonary Fibrosis (IPF); to describe their clinical, serological, and radiological features by a multi-disciplinar team composed by Pulmonologists, Radiologists, and Rheumatologists, comparing IPAF and IPF patients. Methods: In the lasts 2 years, they were enrolled 45 patients with IPAF and 143 with IPF among a total of 506 patients with Interstitial Lung Disease (ILD). All patients were evaluated clinically by both rheumatologists and pulmonologists, also by means of chest high resolution computed tomography (hrCT), pulmonary function tests (PFT), and nailfold videocapillaroscopy. Results: In IPAF cohort the most common characteristics from the clinical, serological and morphological domain were Raynaud's phenomenon (RP) (31.1%) antinuclear antibodies positivity with titre ≥1/320 or any titre for centromeric or nucleolar pattern (17.7%) and nonspecific interstitial pneumonia (68.8%) respectively. The majority of patient (88.9%) had the minimum of 2 criteria at the recruitment. Female gender was more common in IPAF compared to IPF (62.2% vs 23%, p<0.0001) and the mean age of onset was lower in patient with IPAF (66 vs 73, p <0.0001). NVC resulted positive in 2 patients, both without RP. Patients with IPAF showed better performances in PFT than patients with IPF than those with IPF (mean forced vital capacity 83% vs 74%, p =0.01; mean diffusing lung capacity for carbon monoxide 64% vs. 52%, p=0.01). Patients with IPAF less commonly than patients with IPF needed oxygen therapy (44.4% vs 77.6%, p <0.0001) and more commonly showed at hrCT NSIP (68.8% vs 6.9%, p <0.0001) than UIP pattern (0% vs 86%, p <0.0001). Conclusion: IPAF criteria recruit a rare cohort of patients with a disease probably less severe than IPF, even though clinically relevant. Further prospective studies may better define the long-term prognosis of ILD in IPAF. The follow-up of these patients by a multi-disciplinary team may be useful in order to early recognize and treat the new cases of CTDs. Some IPAF criteria probably are useless due to their high specificity for definite CTD and the classification need a revision in the light of the prospective experiences. Nevertheless, IPAF classification can recruit incomplete form or early onset of CTD that can allow a timely treatment in patients without a structured damage. References: [1] Sambataro G, Sambataro D, Torrisi SE, Vancheri A, Pavone M, Rosso R, Schisano M, Crimi C, Pignataro F, Fischer A, Del Papa N, Vancheri C. State of the art in interstitial pneumonia with autoimmune features: a systematic review on retrospective studies and suggestions for further advances. Eur Respir Rev2018:27(148) Disclosure of Interests: None declared